Algorithmic Justice and AI Judges: Reconsidering the Due Process of Law in the Digital Era - Wisnubroto, Aloysius; Suyud Nusanto, Tri (International Journal of Educational Research & Social Sciences, 2025)
The rapid integration of artificial intelligence (AI) into judicial processes presents both opportunities and challenges for contemporary legal systems. Algorithmic decision-making, while promising efficiency and consistency, raises critical concerns regarding the preservation of due process, transparency, and accountability in the administration of justice. This study aims to critically examine the implications of AI judges on procedural fairness and the due process of law in the digital era. Employing a conceptual and comparative research methodology, the study analyzes existing literature, legal frameworks, and emerging practices in AI-assisted adjudication across multiple jurisdictions. The research seeks to identify the potential risks and benefits associated with algorithmic judicial decision-making, including biases embedded in AI systems, challenges to human oversight, and impacts on legal certainty. The expected findings suggest that while AI judges can enhance efficiency, their integration must be carefully regulated to safeguard fundamental legal principles, ensuring that technological innovation does not compromise the fairness and legitimacy of judicial outcomes. The study contributes to ongoing debates on algorithmic justice, offering recommendations for balancing technological advancement with the core values of due process.